Zakat Institution and Maqasid al-Shariʻa: A Study of a Community Empowerment-Based Zakat Program Run by the BAZNAS Bengkulu Province - Toni, Hariya (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2020)
This paper discusses a community empowerment-based zakat program run by the BAZNAS (National Amil Zakat Agency) of Bengkulu Province as well as proves the flexibility of the classical maqāṣid al-sharīʻa in responding to modern development that have not been analyzed by previous researchers. In addition, this paper argues that institutionalizing zakat is not a